Does A Vertebra Fracture Cause A Tumor? A Dorsolumbar Paraspinal Desmoid Tumor: Case Report - Ataizi, Zeki Serdar; Simsek, Gulay; Ataizi, Fulya Colak; Ercan, Serdar (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Extraabdominal desmoid tumors are uncommon soft-tissue tumors. The etiology of the tumor is still unclear. Injury is one of the etiological factors of soft-tissue tumors. A 41-year-old female patient who had a traumatic vertebral body fracture on the thoracic spine was treated conservatively. Two and a half years later, she presented a painful, palpable swelling on the thoracolumbar region. In the present report, was discuss the patient, who underwent a surgery to remove the desmoid tumor (aggressive fibromatosis), within the context of the current literature. The literature on desmoid tumor caused by a trauma is rare. This is the first case that demonstrates an extraabdominal desmoid tumor following a spinal fracture. The swelling on the region of the trauma must be examined carefully and desmoid tumor must be kept in mind as a possible diagnosis.
Keywords: trauma; vertebral fracture; extra-abdominal desmoid tumor